34. Accomplishing the requirements within the new decree 159/2016: Comparative study of eddy currents induced in a human phantom moving near different MRI scanners. (December 2018) - Gurrera, D.; Gallias, K.K.; Spanò, M.; Abbate, B.F.; D'Alia, F.; Iacoviello, G.; Caputo, V.
Abstract : Purpose: In order to provide adequate risk-reducing procedures for MRI personnel (radiographers, anaesthetists, physicists, nurses, technicians, cleaners, etc.), different studies have been developed in the past years. Further to those, in the present work risk assessment concerned with currents induced by non-uniform static magnetic fields in MRI operators performing different tasks in proximity of the scanner has been investigated across a set of different 1.5 T MRI scanners. Methods: The first step has been to empirically map the magnetic field around the different scanners and to select a proper adult human body as a heterogeneous volume conductor model. Then, upon observing the way tasks are executed by different categories of MRI personnel, we provided our phantom with the riskiest behaviour and performed simulations in order to possibly predict eddy currents actually induced in a human body. Results: Our simulations confirm that the induced fields and currents should not be ignored at ultrahigh B-fields. Indeed, it is possible to observe real procedures that, according to our analysis, could possibly generate E-fields near the level of physiological significance under some circumstances. Conclusions: In view of the exposed results, the research here presented, while yielding a new empirical sample to the investigated problem, provides further confirmation to some previous findings. Specifically, it gives further evidence that apart from the requirements of the decree 159 – which our analysis has found always accomplished – there is still room for undesired levels of induced E-fields that a detailed study of movement in ultrahigh static B-fields could reduce below the threshold of physiological significance.